UV-cured organic / inorganic hybrid low-fluorine-content wear-resistant anti-fingerprint coating and preparation method thereof
By combining the fluorine-containing polyurethane acrylate oligomer with a modified silica sol, UV cured organic/inorganic hybrid low-fluorine-resistant and anti-fingerprint coating was prepared, which solved the problems of large fluorine content and poor wear resistance of the existing coating, and achieved the improvement of high transparency, hardness, wear resistance and anti-fingerprint performance.
Patent Information
- Application Number
- CN202411988153.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing anti-fingerprint coating has a large fluorine content and poor surface wear resistance, making it difficult to meet the low refractive index, high light transmittance, high surface hardness, strong scratch resistance and hydrophobic oleophobic antifouling properties.
The fluoropolyurethane acrylate oligomer was synthesized using perfluoropolyether glycol and polycarbonate diol, and combined with modified silica sol, photoinitiator, leveling agent and defoaming agent to prepare a UV curing organic/inorganic hybrid low fluorine-resistant and wear-resistant fingerprint coating through ultraviolet curing.
The coating is achieved with high transparency, low surface energy, improved hardness and wear resistance, and has excellent fingerprint resistance and hydrophobicity, which can maintain performance under high friction conditions.
Smart Images

Figure BDA0005223057400000021 
Figure BDA0005223057400000051 
Figure BDA0005223057400000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocurable resins and coatings, and in particular to a UV-curable organic / inorganic hybrid low-fluorine-containing wear-resistant anti-fingerprint coating and a preparation method thereof. Background Art
[0002] With the advancement of science and technology and social development, polymer-based coatings have attracted widespread attention due to their unique properties and have been applied in many fields. One of the core functions of such coatings is to provide protection for the substrate. However, compared with metal- and ceramic-based coatings, polymer-based coatings are generally weaker in mechanical properties such as hardness and wear resistance due to the inherent properties of the polymer materials themselves. Friction between the contact surfaces of materials leads to surface loss, which not only shortens the service life of the material, but also causes a large amount of energy consumption at the macro level. Therefore, the research and development of polymer-based coatings with improved mechanical properties is of great significance to improve the durability and energy efficiency of materials.
[0003] UV light curing has been widely used in the preparation of transparent coatings, but the problem that transparent coatings are easily contaminated by fingerprints and other stains cannot be ignored. In recent years, some researchers have proposed some studies to solve the anti-fingerprint performance of coatings. Chen Wei has used isocyanate to modify the silicone resin composition, which can greatly improve the surface hardness and scratch resistance of plastics; but the coating cannot simultaneously have low refractive index, high light transmittance, high surface hardness, strong scratch resistance and hydrophobic and oleophobic antifouling properties, so it is difficult to meet the requirements of protective coatings. Patent US15029867 proposes a fluorine-containing anti-fingerprint additive for UV coatings, which can improve the anti-fingerprint and wear resistance of the coating. However, the compound is only used as a functional additive and is not the main resin component of the UV coating. Therefore, the wear resistance of the coating is not ideal and cannot meet the requirements of high wear resistance. Fluorine-containing compounds are widely used because of their low surface energy, high stability and hydrophobicity. However, the use of large doses of fluorine-containing compounds will cause environmental pollution, bioaccumulation, health risks and ecological damage, and effective measures need to be taken to reduce their emissions and pollution. Therefore, how to obtain a UV-curable organic / inorganic hybrid low-fluorine-containing wear-resistant anti-fingerprint coating and a preparation method thereof are technical problems that need to be solved at present. Summary of the invention
[0004] The object of the present invention is to provide a UV-curable organic / inorganic hybrid low-fluorine wear-resistant anti-fingerprint coating and a preparation method thereof, so as to solve the technical problems of the existing anti-fingerprint coating having a large fluorine content and poor surface wear resistance.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a UV-curable organic / inorganic hybrid low-fluorine wear-resistant anti-fingerprint coating, which is prepared from raw materials including the following mass percentages:
[0007]
[0008] Furthermore, the preparation method of the fluorine-containing polyurethane acrylate oligomer comprises the following steps:
[0009] S1. In a N2 environment, a perfluoropolyether diol, a polycarbonate diol, a diisocyanate and an organic metal catalyst are mixed and reacted to obtain an NCO-terminated prepolymer;
[0010] S2, adding a polymerization inhibitor and a capping agent monomer to the prepolymer to react to obtain a fluorine-containing polyurethane acrylate resin;
[0011] The molar ratio of the perfluoropolyether diol to the polycarbonate diol is 1:5-10; the molar ratio of the polycarbonate diol to the diisocyanate is 1:1-2, and the amount of the organic metal catalyst is 0.1-2% of the total mass of the perfluoropolyether diol, the polycarbonate diol and the diisocyanate;
[0012] The dosage of the polymerization inhibitor is 0.01-0.1% of the weight of the prepolymer, and the molar ratio of the diisocyanate to the end-capping agent monomer is 2:1-2.
[0013] Further, the perfluoropolyether diol comprises one or more of Italian SOLVAY FLUOROLINK D4000, domestic Yuyao Huihong FD-162, FD-163, FD-164 and domestic Wuhan Lanabai No. 1937;
[0014] The polycarbonate diol comprises one or more of UH-200, PH-200 and BH-200 in the Ube PCDL series, Asahi Kasei G3452, G3450J, T4672, T4692, T4691 and T5652, Kuraray C-2050 and C-2090, and domestic Guangdong Wengjiang PC06349 and Munafei MNF3230;
[0015] The diisocyanate comprises one or more of isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate and hexamethylene diisocyanate; and the organic metal catalyst comprises one or more of dibutyltin dilaurate, stannous octoate and organic bismuth.
[0016] Furthermore, the polymerization inhibitor comprises one or more of 4-methoxyphenol, hydroquinone and 2,6-di-tert-butyl-p-methylphenol; the end-capping agent monomer comprises one or more of hydroxyethyl methacrylate, hydroxyethyl acrylate, 2-ethoxyethyl acrylate, 2-cyanoacrylate, β-hydroxypropyl acrylate, β-hydroxypropyl methacrylate, pentaerythritol triacrylate and dipentaerythritol pentaacrylate.
[0017] Furthermore, in the step S1, the reaction temperature is 70-90° C., and the reaction time is 2-4 hours; in the step S2, the reaction temperature is 60-80° C., and the reaction time is 3-5 hours.
[0018] Furthermore, the preparation method of the modified silica sol comprises the following steps:
[0019] S3, tetraethyl orthosilicate and anhydrous ethanol are mixed at 20-40° C., and the temperature is raised while stirring. After reaching the reaction temperature, a hydrochloric acid solution catalyst is added dropwise to adjust the pH to 3-4. After the addition is completed, the reaction is continued for a certain period of time to obtain a hydrolysis solution;
[0020] S4, adding silanes with different functional groups to the hydrolysis solution to react, and aging to obtain modified silica sol;
[0021] In the step S3, the mixing time is 15 to 30 minutes, the reaction temperature is 30 to 50° C., and the reaction time is 2 to 3 hours; in the step S4, the reaction temperature is 50 to 70° C., the reaction time is 4 to 8 hours, and the aging time is 3 to 5 days.
[0022] Furthermore, the molar ratio of the tetraethyl orthosilicate, the silanes with different functional groups and the anhydrous ethanol is 1:0.1-5:1-10; the silane comprises one or more of methyltrimethoxysilane, methyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, methacryloxypropyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, perfluorodecyltriethoxysilane, (3-mercaptopropyl)trimethoxysilane, tridecafluorooctyltrimethoxysilane, perfluoropolyethertrimethoxysilane, dodecyltrimethoxysilane and dodecyltriethoxysilane.
[0023] Further, the reactive diluent comprises one or more of isobornyl acrylate, dicyclopentenyl acrylate, 1,6-hexanediol diacrylate, diethylene glycol diacrylate and trimethylolpropane triacrylate;
[0024] The photoinitiator comprises one or more of 1-hydroxycyclohexyl phenyl ketone, benzoin diethyl ether, 2-hydroxy-2-methyl-1-phenylpropanone, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester; the leveling agent comprises one or more of German BYK-3455, BYK-3550 and BYK333; the defoamer comprises one or more of American Dow AFE-1430, German BYK-066N, domestic Datian AT-99 and German AS-6800.
[0025] The present invention also provides a method for preparing a UV-curable organic / inorganic hybrid low-fluorine-containing wear-resistant anti-fingerprint coating, comprising the following steps:
[0026] The fluorine-containing polyurethane acrylate oligomer, the reactive diluent, the modified silica sol, the photoinitiator, the leveling agent and the defoaming agent are mixed, kept still in a dark place and stirred until the mixture is homogeneous and transparent to obtain a sample;
[0027] The sample is coated on the surface of a dry substrate and cured by ultraviolet light to obtain a UV-cured organic / inorganic hybrid low-fluorine-containing wear-resistant and anti-fingerprint coating.
[0028] Furthermore, the UV curing time is 30 to 300 seconds.
[0029] Beneficial effects of the present invention:
[0030] The UV curable organic / inorganic hybrid low-fluorine wear-resistant hydrophobic coating material provided by the invention is compounded with fluorine-containing polyurethane acrylate oligomer, reactive diluent, modified silica sol, photoinitiator, leveling agent and defoaming agent, and is cured by ultraviolet light. The coating prepared by fluorine-containing polyurethane acrylate oligomer and reactive diluent itself has transparency and low surface energy, and the inorganic components of the coating are increased after the introduction of modified silica sol, and the light transmittance of the coating is not affected. At the same time, the volume shrinkage of the coating can be reduced, and the hardness and wear resistance of the coating can be improved. The results of the embodiment show that it has a contact angle of more than 110°, a light transmittance of more than 90%, and can still maintain hydrophobicity after rubbing 2000 times with 0000# steel wool at a weight of 1kg; and has excellent anti-fingerprint performance that can remove fingerprints by wiping with a paper towel less than once.
[0031] The invention introduces perfluoropolyether diol into polycarbonate diol by a chemical method, and the prepared fluorine-containing polyurethane acrylate oligomer has both low surface energy and chemical resistance.
[0032] The present invention improves the compatibility of organic and inorganic components with different properties by preparing modified silica sol through sol-gel technology, and the reaction can be carried out at room temperature. The prepared hybrid coating combines the high hardness, wear resistance, scratch resistance, high temperature resistance and solvent resistance of inorganic materials, and the good flexibility and easy processing of organic materials. The preparation method is simple, and combined with ultraviolet curing technology, the use of solvents and energy is greatly saved, making the preparation process more environmentally friendly. DETAILED DESCRIPTION
[0033] The present invention provides a UV-curable organic / inorganic hybrid low-fluorine wear-resistant anti-fingerprint coating, which is prepared from raw materials including the following mass percentages:
[0034]
[0035] In the present invention, the amount of the fluorine-containing polyurethane acrylate oligomer is preferably 35 to 80% by mass, more preferably 40 to 75%, and even more preferably 45 to 70%.
[0036] In the present invention, the amount of the active diluent is preferably 15-25% by mass, more preferably 18-22%, and even more preferably 20%.
[0037] In the present invention, the amount of the modified silica sol is preferably 5-25% by mass, more preferably 10-20%, and more preferably 15%.
[0038] In the present invention, the amount of the photoinitiator is preferably 2-3% by mass, and more preferably 2.5-2.8% by mass.
[0039] In the present invention, the amount of the leveling agent is preferably 0.2-0.4% by mass, and more preferably 0.3% by mass.
[0040] In the present invention, the amount of the defoaming agent is preferably 0.2-0.4% by mass, and more preferably 0.3% by mass.
[0041] The preparation method of the fluorine-containing polyurethane acrylate oligomer comprises the following steps:
[0042] S1. In a N2 environment, a perfluoropolyether diol, a polycarbonate diol, a diisocyanate and an organic metal catalyst are mixed and reacted to obtain an NCO-terminated prepolymer;
[0043] S2. Adding a polymerization inhibitor and a capping agent monomer to the above prepolymer to react and obtain a fluorine-containing polyurethane acrylate resin.
[0044] In the present invention, the molar ratio of the perfluoropolyether diol to the polycarbonate diol is 1:5-10, preferably 1:6-9, and more preferably 1:7-8; the molar ratio of the polycarbonate diol to the diisocyanate is 1:1-2, preferably 1:1.2-1.8, and more preferably 1:1.5. The amount of the organic metal catalyst is 0.1-2% of the total mass of the perfluoropolyether diol, the polycarbonate diol and the diisocyanate, preferably 0.2-1%, and more preferably 0.2-0.3%.
[0045] In the present invention, the amount of the polymerization inhibitor is 0.01-0.1% of the prepolymer mass, preferably 0.02-0.08%, more preferably 0.03-0.06%, and the molar ratio of diisocyanate to end-capping agent monomer is 2:1-2, preferably 2:1.
[0046] In the present invention, the perfluoropolyether diol is preferably one or more of Italian SOLVAYFLUOROLINKD 4000, domestic Yuyao Huihong FD-162, FD-163, FD-164 and domestic Wuhan Lanabai No. 1937;
[0047] The polycarbonate diol is preferably one or more of UH-200, PH-200 and BH-200 in the Ube PCDL series, Asahi Kasei G3452, G3450J, T4672, T4692, T4691 and T5652, Kuraray C-2050 and C-2090, and domestic Guangdong Wengjiang PC06349 and Munafei MNF3230;
[0048] The diisocyanate is preferably one or more of isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate and hexamethylene diisocyanate; the organic metal catalyst comprises one or more of dibutyltin dilaurate, stannous octoate and organic bismuth.
[0049] In the present invention, the polymerization inhibitor is preferably one or more of 4-methoxyphenol, hydroquinone and 2,6-di-tert-butyl-p-methylphenol; the end-capping agent monomer includes one or more of hydroxyethyl methacrylate, hydroxyethyl acrylate, 2-ethoxyethyl acrylate, 2-cyanoacrylate, β-hydroxypropyl acrylate, β-hydroxypropyl methacrylate, pentaerythritol triacrylate and dipentaerythritol pentaacrylate. In the present invention, when the raw materials are more than two of the above, the present invention has no special restrictions on the ratio of different raw materials, and can be adjusted according to actual needs.
[0050] In the present invention, in the step S1, the reaction temperature is 70-90°C, preferably 75-85°C, and more preferably 80°C; the reaction time is 2-4h, and preferably 3h; in the step S2, the reaction temperature is 60-80°C, preferably 65-75°C, and more preferably 70-72°C; the reaction time is 3-5h, and preferably 4h.
[0051] In the present invention, in step S1, the reaction is carried out under stirring, and the stirring speed is 200-400 rpm, preferably 300 rpm.
[0052] In the present invention, the preparation method of the modified silica sol comprises the following steps:
[0053] S3, tetraethyl orthosilicate and anhydrous ethanol are mixed at 20-40° C., and the temperature is raised while stirring. After reaching the reaction temperature, a hydrochloric acid solution catalyst is added dropwise to adjust the pH to 3-4. After the addition is completed, the reaction is continued for a certain period of time to obtain a hydrolysis solution;
[0054] S4. Add silanes with different functional groups into the hydrolysis solution for reaction, and age to obtain modified silica sol.
[0055] In the present invention, in the step S3, the mixing time is 15 to 30 minutes, preferably 20 to 25 minutes; the reaction temperature is 30 to 50°C, preferably 35 to 45°C; the reaction time is 2 to 3 hours, preferably 2 hours; in the step S4, the reaction temperature is 50 to 70°C, preferably 55 to 65°C, more preferably 60 to 62°C; the reaction time is 4 to 8 hours, preferably 5 to 7 hours, more preferably 6 hours; the aging time is 3 to 5 days, preferably 4 days.
[0056] In the present invention, the molar ratio of tetraethyl orthosilicate, silanes with different functional groups and anhydrous ethanol is 1:0.1-5:1-10, preferably 1:0.25-4:2-9, and more preferably 1:0.25-3:4-8.
[0057] In the present invention, the silane is preferably one or more of methyltrimethoxysilane, methyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, methacryloxypropyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, perfluorodecyltriethoxysilane, (3-mercaptopropyl)trimethoxysilane, tridecafluorooctyltrimethoxysilane, perfluoropolyethertrimethoxysilane, dodecyltrimethoxysilane and dodecyltriethoxysilane. In the present invention, when the raw material is more than two kinds, the present invention has no special limitation on different raw material ratios, and can be adjusted according to actual needs.
[0058] In the present invention, the reactive diluent is preferably one or more of isobornyl acrylate, dicyclopentenyl acrylate, 1,6-hexanediol diacrylate, diethylene glycol diacrylate and trimethylolpropane triacrylate;
[0059] The photoinitiator is preferably one or more of 1-hydroxycyclohexyl phenyl ketone, benzoin diethyl ether, 2-hydroxy-2-methyl-1-phenylpropanone, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester; the leveling agent includes one or more of German BYK-3455, BYK-3550 and BYK333; the defoamer includes one or more of American Dow AFE-1430, German BYK-066N, domestic Datian AT-99 and German AS-6800. In the present invention, when the raw materials are more than two of the above, the present invention has no special limitation on the different raw material ratios, and can be adjusted according to actual needs.
[0060] The present invention also provides a method for preparing a UV-curable organic / inorganic hybrid low-fluorine-containing wear-resistant anti-fingerprint coating, comprising the following steps:
[0061] The fluorine-containing polyurethane acrylate oligomer, the reactive diluent, the modified silica sol, the photoinitiator, the leveling agent and the defoaming agent are mixed, kept still in a dark place and stirred until the mixture is homogeneous and transparent to obtain a sample;
[0062] The sample is coated on the surface of a dry substrate and cured by ultraviolet light to obtain a UV-cured organic / inorganic hybrid low-fluorine-containing wear-resistant and anti-fingerprint coating.
[0063] In the present invention, the UV curing is preferably carried out under a UV-LED lamp, and the UV curing time is 30 to 300 seconds, preferably 50 to 200 seconds, and more preferably 150 to 180 seconds. During the UV curing process, the photoinitiator absorbs UV light and converts into free radicals, which initiate cross-linking of double bonds in the fluorinated polyurethane acrylate oligomer, the reactive diluent, and the modified silica sol, thereby curing the coating.
[0064] In the present invention, the coating is to coat the sample on the surface of a substrate that has been repeatedly cleaned and dried using a 30 μm wet film preparation device, and the substrate comprises a plastic substrate, a glass substrate or a metal substrate.
[0065] In the present invention, the coating method is preferably spread coating; the thickness of the spread coating is preferably 25 to 100 μm, more preferably 25 to 50 μm, and more preferably 30 μm.
[0066] In the present invention, the substrate is preferably glass, metal or plastic.
[0067] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0068] Example 1
[0069] (1) Clean the surface of the slide and dry it for later use;
[0070] (2) adding 0.5 g (15.60%) 1,6-hexanediol diacrylate and 0.125 g (3.90%) modified silica sol to 2.5 g (78.00%) fluorine-containing polyurethane acrylate oligomer, and letting the mixture stand in a container for 30 min, adding 0.06 g (1.88%) photoinitiator 1-hydroxycyclohexyl phenyl ketone, 0.01 g (0.31%) leveling agent BYK333 and 0.01 g (0.31%) defoaming agent AFE-1430 to the container, and stirring the mixture under magnetic force in a dark place until the mixture is homogeneous and transparent, thereby obtaining a mixed coating;
[0071] (3) applying the mixed coating to a thickness of 30±1 μm on a cleaned glass slide;
[0072] (4) The coated substrate is placed under a UV-LED lamp for ultraviolet irradiation for 90 seconds to obtain a transparent coating.
[0073] The preparation process of the fluorinated polyurethane acrylate oligomer comprises the following steps:
[0074] Under N2, 0.3g (0.5mmol) of perfluoropolyether diol FD-162 (Mn = 600g / mol), 9g (4.5mmol) of dehydrated polycarbonate diol UH-200 (Mn = 2000g / mol), and 2.24g (10mmol) of isophorone diisocyanate were added to a three-necked flask in sequence, and 0.3% of dibutyltin dilaurate was added. The mechanical stirring speed was 300rpm, and the mixture was reacted at 80°C for 3h. When the NCO% was titrated to reach the theoretical value, 1.3g (10mmol) of end-capping agent hydroxyethyl methacrylate and 0.1% of hydroquinone were added, and the mixture was reacted at 70°C for 4h. When the NCO% was titrated to ≤0.06%, the reaction was terminated to obtain a fluorinated polyurethane acrylate oligomer having the following structure:
[0075]
[0076] The structures of R1 and R2 are as follows:
[0077]
[0078] Wherein x, y, p and q represent integers of the number of repeating units. The structures of R1 and R2 in the whole text are all of this type and will not be described in detail later.
[0079] The structure of R is
[0080]
[0081] The modified silica sol preparation process includes the following steps:
[0082] 10.4 g (0.05 mol) of ethyl orthosilicate and 6.9 g (0.15 mol) of anhydrous ethanol were added to a three-necked flask, heated to 40°C, stirred for 15 min, and the rotation speed was 500 rpm. Then, an acid solution consisting of 0.062 ml of hydrochloric acid and 3.15 g (0.175 mol) of deionized water was added dropwise, stirred for 2 h, and then 12.42 g (0.05 mol) of 3-(methacryloyloxy)propyltrimethoxysilane was added. The temperature was raised to 60°C, reacted for 6 h, and aged for 4 days to obtain a modified silica sol, the structure of which is as follows:
[0083]
[0084] Where M and M 1 The structure is as follows:
[0085]
[0086] Example 2
[0087] (1) Clean the surface of the slide and dry it for later use;
[0088] (2) adding 1.0 g (13.81%) trimethylolpropane triacrylate and 1.0 g (13.81%) modified silica sol to 5.0 g (69.06%) fluorine-containing polyurethane acrylate oligomer, and letting the mixture stand in a container for 30 min, adding 0.21 g (2.9%) photoinitiator benzoin diethyl ether, 0.02 g (0.28%) leveling agent BYK-3550 and 0.01 g (0.14%) defoaming agent BYK-066N to the container, and stirring the mixture under magnetic force in a dark place until the mixture is homogeneous and transparent, thereby obtaining a mixed coating;
[0089] (3) applying the mixed coating to a thickness of 30±1 μm on a cleaned glass slide;
[0090] (4) The coated substrate is placed under a UV-LED lamp for ultraviolet irradiation for 90 seconds to obtain a transparent coating.
[0091] The preparation process of the fluorinated polyurethane acrylate oligomer comprises the following steps:
[0092] Under the protection of N2 atmosphere, 1.0g (0.5mmol) of perfluoropolyether diol FD-164 (Mn = 2000g / mol), 9g (4.5mmol) of dehydrated polycarbonate diol PH-200 (Mn = 2000g / mol), and 2.24g (10mmol) of isophorone diisocyanate were added to a three-necked flask in sequence, and 0.3% of dibutyltin dilaurate was added. The mechanical stirring speed was 300rpm, and the reaction was carried out at 80°C for 3h. The NCO% was titrated to reach the theoretical value, and then 2.98g (10mmol) of the end-capping agent pentaerythritol triacrylate and 0.05% of 4-methoxyphenol were added dropwise, and the reaction was carried out at 70°C for 4h. The reaction was terminated when the titration NCO% was ≤0.06%, and a fluorinated polyurethane acrylate oligomer was obtained, and the structure was as follows:
[0093]
[0094] Where R 1 The structure is as follows:
[0095]
[0096] The modified silica sol preparation process includes the following steps:
[0097] 10.4 g (0.05 mol) of ethyl orthosilicate and 6.9 g (0.15 mol) of anhydrous ethanol were added to a three-necked flask, heated to 40°C, stirred for 15 min, and the speed was 500 rpm. Then, an acid solution consisting of 0.062 ml of hydrochloric acid and 3.15 g (0.175 mol) of deionized water was added dropwise, stirred for 2 h, and then 7.41 g (0.05 mol) of vinyltrimethoxysilane was added. The temperature was raised to 60°C, reacted for 6 h, and aged for 4 days to obtain a modified silica sol, the structure of which is as follows:
[0098]
[0099] Where M and M 2 The structure is as follows:
[0100]
[0101] Example 3
[0102] (1) Clean the surface of the slide and dry it for later use;
[0103] (2) adding 1.0 g (14.86%) isobornyl acrylate and 0.5 g (7.43%) modified silica sol to 5.0 g (74.29%) fluorinated polyurethane acrylate oligomer, and letting the mixture stand in a container for 30 min, adding 0.20 g (2.97%) photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone, 0.01 g (0.15%) leveling agent BYK-3455 and 0.02 g (0.3%) defoaming agent AT-99 to the container, and stirring the mixture under magnetic force in the dark until the mixture is homogeneous and transparent to obtain a mixed coating;
[0104] (3) applying the mixed coating to a thickness of 30±1 μm on a cleaned glass slide;
[0105] (4) The coated substrate is placed under a UV-LED lamp for ultraviolet irradiation for 90 seconds to obtain a transparent coating.
[0106] The preparation process of the fluorinated polyurethane acrylate oligomer comprises the following steps:
[0107] Under the protection of N2 atmosphere, 0.65g (0.5mmol) perfluoropolyether diol FD-163 (Mn = 1300g / mol), 9g (4.5mmol) dehydrated polycarbonate diol BH-200 (Mn = 2000g / mol), and 2.24g (10mmol) isophorone diisocyanate were added to a three-necked flask in sequence, and 0.3% dibutyltin dilaurate was added. The mechanical stirring speed was 300rpm, and the reaction was carried out at 80°C for 3h. The NCO% was titrated to reach the theoretical value, and then 5.24g (10mmol) of dipentaerythritol pentaacrylate was added dropwise as a capping agent and 0.1% of 2,6-di-tert-butyl-p-methylphenol. The reaction was carried out at 70°C for 4h. The reaction was terminated when the NCO% was ≤0.06%, and a fluorinated polyurethane acrylate oligomer was obtained, and the structure was as follows:
[0108]
[0109] Where R 2 The structure is as follows:
[0110]
[0111] The modified silica sol preparation process includes the following steps:
[0112] 10.4 g (0.05 mol) of ethyl orthosilicate and 6.9 g (0.15 mol) of anhydrous ethanol were added to a three-necked flask, heated to 40°C, stirred for 15 min, and the rotation speed was 500 rpm. Then, an acid solution consisting of 0.062 ml of hydrochloric acid and 3.15 g (0.175 mol) of deionized water was added dropwise, stirred for 2 h, and then 17.33 g (0.05 mol) of hexadecyltrimethoxysilane was added. The temperature was raised to 60°C, reacted for 6 h, and aged for 4 days to obtain a modified silica sol, the structure of which is as follows:
[0113]
[0114] Where M and M 3 The structure is as follows:
[0115]
[0116] Example 4
[0117] (1) Clean the surface of the slide and dry it for later use;
[0118] (2) adding 0.5 g (14.30%) diethylene glycol diacrylate and 0.375 g (10.73%) modified silica sol to 2.5 g (71.53%) fluorine-containing polyurethane acrylate oligomer, and letting the mixture stand in a container for 30 min, adding 0.1 g (2.86%) photoinitiator 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, 0.01 g (0.29%) leveling agent BYK333 and 0.01 g (0.29%) defoaming agent AS-6800 to the container, and stirring the mixture under magnetic force in a dark place until the mixture is homogeneous and transparent, thereby obtaining a mixed coating;
[0119] (3) applying the mixed coating to a thickness of 30±1 μm on a cleaned glass slide;
[0120] (4) The coated substrate is placed under a UV-LED lamp for ultraviolet irradiation for 90 seconds to obtain a transparent coating.
[0121] The preparation process of the fluorinated polyurethane acrylate oligomer comprises the following steps:
[0122] Under the protection of N2 atmosphere, 0.52g (0.5mmol) perfluoropolyether diol Wuhan Lana White 1937 (Mn = 1040g / mol), 9g (4.5mmol) dehydrated polycarbonate diol G3452 (Mn = 2000g / mol), 2.24g (10mmol) isophorone diisocyanate were added to a three-necked flask in sequence, and 0.3% dibutyltin dilaurate was added. The mechanical stirring speed was 300rpm, and the reaction was carried out at 80 ° C for 3h, and the NCO% was titrated to reach the theoretical value, and then 0.65g (5mmol) of hydroxyethyl methacrylate and 1.49g (5mmol) of pentaerythritol triacrylate were added dropwise as end-capping agents and 0.05% of hydroquinone, and the reaction was carried out at 70 ° C for 4h. The titration of NCO% ≤ 0.06% was completed to obtain a fluorinated polyurethane acrylate oligomer, the structure of which is as follows:
[0123]
[0124] Where R a and R b The structure is as follows:
[0125]
[0126] The modified silica sol preparation process includes the following steps:
[0127] 10.4 g (0.05 mol) of ethyl orthosilicate and 6.9 g (0.15 mol) of anhydrous ethanol were added to a three-necked flask, heated to 40°C, stirred for 15 min, and the rotation speed was 500 rpm. Then, an acid solution consisting of 0.062 ml of hydrochloric acid and 3.15 g (0.175 mol) of deionized water was added dropwise, stirred for 2 h, and then 9.36 g (0.02 mol) of tridecafluorooctyltrimethoxysilane was added dropwise. The temperature was raised to 60°C, reacted for 6 h, and aged for 4 days to obtain a modified silica sol, the structure of which is as follows:
[0128]
[0129] Where M and M 4 The structure is as follows:
[0130]
[0131] Example 5
[0132] (1) Clean the surface of the slide and dry it for later use;
[0133] (2) adding 1.0 g (14.54%) of dicyclopentenyl acrylate and 0.75 g (10.90%) of modified silica sol to 5.0 g (72.67%) of fluorinated polyurethane acrylate oligomer, and letting the mixture stand in a container for 30 min, adding 0.1 g (1.45%) of photoinitiator 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester, 0.01 g (0.14%) of leveling agent BYK-3455 and 0.02 g (0.3%) of defoaming agent AFE-1430 to the container, and stirring the mixture under magnetic force in a dark place until the mixture is homogeneous and transparent, thereby obtaining a mixed coating;
[0134] (3) Apply the mixed coating to a thickness of 30±1 um on a cleaned glass slide.
[0135] (4) The coated substrate is placed under a UV-LED lamp for ultraviolet irradiation for 90 seconds to obtain a transparent coating.
[0136] The preparation process of the fluorinated polyurethane acrylate oligomer comprises the following steps:
[0137] Under the protection of N2 atmosphere, 0.65g (0.5mmol) perfluoropolyether diol FD-163 (Mn = 1300g / ol), 9g (4.5mmol) dehydrated polycarbonate diol PC06349 (Mn = 2000g / mol), and 2.24g (10mmol) isophorone diisocyanate were added to a three-necked flask in sequence, and 0.3% dibutyltin dilaurate was added. The mechanical stirring speed was 300rpm, and the reaction was carried out at 80°C for 3h. The NCO% was titrated to reach the theoretical value, and then 0.65g (5mmol) hydroxyethyl methacrylate and 2.62g dipentaerythritol pentaacrylate were added dropwise as end-capping agents and 0.1% 4-methoxyphenol. The reaction was carried out at 70°C for 4h. The reaction was terminated when the NCO% was ≤0.06% by titration, and a fluorinated polyurethane acrylate oligomer was obtained, and the structure was as follows:
[0138]
[0139] Where R c and R d The structure is as follows:
[0140]
[0141] The modified silica sol preparation process includes the following steps:
[0142] 10.4 g (0.05 mol) of ethyl orthosilicate and 6.9 g (0.15 mol) of anhydrous ethanol were added to a three-necked flask, heated to 40°C, stirred for 15 min, and rotated at 500 rpm. Then, an acid solution consisting of 0.062 ml of hydrochloric acid and 3.15 g (0.175 mol) of deionized water was added dropwise, stirred for 2 h, and then 9.17 g (0.05 mol) (3-mercaptopropyl) trimethoxysilane was added dropwise. The temperature was raised to 60°C, reacted for 6 h, and aged for 4 days to obtain a modified silica sol, the structure of which is as follows
[0143]
[0144] Where M and M 5 The structure is as follows
[0145]
[0146] Example 6
[0147] (1) Clean the surface of the slide and dry it for later use;
[0148] (2) adding 0.5 g (12.92%) 1,6-hexanediol diacrylate and 0.75 g (19.38%) modified silica sol to 2.5 g (64.60%) fluorine-containing polyurethane acrylate oligomer, and letting the mixture stand in a container for 30 min, adding 0.1 g (2.6%) photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 0.01 g (0.25%) leveling agent BYK-3550 and 0.01 g (0.25%) defoaming agent BYK-066N to the container, and stirring the mixture under magnetic force in a dark place until the mixture is homogeneous and transparent, thereby obtaining a mixed coating;
[0149] (3) Apply the mixed coating to a thickness of 30±1 um on a cleaned glass slide.
[0150] (4) The coated substrate is placed under a UV-LED lamp for ultraviolet irradiation for 90 seconds to obtain a transparent coating.
[0151] The preparation process of the fluorinated polyurethane acrylate oligomer comprises the following steps:
[0152] Under the protection of N2 atmosphere, 0.3g (0.5mmol) perfluoropolyether diol FD-162 (Mn = 600g / mol), 9g (4.5mmol) dehydrated polycarbonate diol MNF3230 (Mn = 2000g / mol), and 2.24g (10mmol) isophorone diisocyanate were added to a three-necked flask in sequence, and 0.3% dibutyltin dilaurate was added. The mechanical stirring speed was 300rpm, and the reaction was carried out at 80°C for 3h. The NCO% was titrated to reach the theoretical value, and then 2.62g (5mmol) dipentaerythritol pentaacrylate and 1.49g (5mmol) pentaerythritol triacrylate were added dropwise as end-capping agents and 0.05% 2,6-di-tert-butyl-p-methylphenol. The reaction was carried out at 70°C for 4h. The titration NCO% was ≤0.06% and the reaction was completed to obtain a fluorinated polyurethane acrylate oligomer with the following structure:
[0153]
[0154] Where R e and R f The structure is as follows:
[0155]
[0156] The modified silica sol preparation process includes the following steps:
[0157] 10.4 g (0.05 mol) of ethyl orthosilicate and 6.9 g (0.15 mol) of anhydrous ethanol were added to a three-necked flask, heated to 40°C, stirred for 15 min, and rotated at 500 rpm. Then, an acid solution consisting of 0.062 ml of hydrochloric acid and 3.15 g (0.175 mol) of deionized water was added dropwise, stirred for 2 h, and then 6.10 g (0.01 mol) of perfluorodecyltriethoxysilane was added dropwise. The temperature was raised to 60°C, reacted for 6 h, and aged for 4 days to obtain a modified silica sol, the structure of which is as follows
[0158]
[0159] Where M and M 6 The structure is as follows
[0160]
[0161] Comparative Example 1
[0162] (1) Clean the surface of the slide and dry it for later use;
[0163] (2) adding 0.5 g (16.03%) 1,6-hexanediol diacrylate to 2.5 g (80.13%) fluorine-containing polyurethane acrylate oligomer in a container and letting it stand for 30 min, adding 0.1 g (3.2%) photoinitiator 1-hydroxycyclohexyl phenyl ketone, 0.01 g (0.32%) leveling agent BYK333 and 0.01 g (0.32%) defoaming agent AFE-1430 into the container, and stirring with a magnetic force in the dark until the mixture is homogeneous and transparent to obtain a mixed coating;
[0164] (3) applying the mixed coating to a thickness of 30±1 μm on a cleaned glass slide;
[0165] (4) The coated substrate is placed under a UV-LED lamp for ultraviolet irradiation for 90 seconds to obtain a transparent coating.
[0166] The preparation process of the fluorinated polyurethane acrylate oligomer comprises the following steps:
[0167] Under the protection of N2 atmosphere, 0.3g (0.5mmol) of perfluoropolyether diol FD-162 (Mn=600g / mol), 9g (4.5mmol) of dehydrated polycarbonate diol UH-200 (Mn=2000g / mol), and 2.24g (10mmol) of isophorone diisocyanate were added into a three-necked flask in sequence, and 0.3% of dibutyltin dilaurate was added. The mechanical stirring speed was 300rpm, and the mixture was reacted at 80°C for 3h. The NCO% was titrated to reach the theoretical value, and then 1.3g (10mmol) of end-capping agent hydroxyethyl methacrylate and 0.1% of hydroquinone were added dropwise. The mixture was reacted at 70°C for 4h. The reaction was terminated when the titration NCO% was ≤0.06%, and a fluorinated polyurethane acrylate oligomer was obtained.
[0168] The structural formula of the fluorine-containing polyurethane acrylate oligomer is the same as that of Example 1.
[0169] Comparative Example 2
[0170] (1) Clean the surface of the slide and dry it for later use;
[0171] (2) adding 1.0 g (16%) of trimethylolpropane triacrylate to 5.0 g (80%) of fluorinated polyurethane acrylate oligomer, and letting the mixture stand in a container for 30 min, adding 0.21 g (3.4%) of photoinitiator benzoin diethyl ether, 0.02 g (0.3%) of leveling agent BYK-3550, and 0.01 g (0.2%) of defoaming agent BYK-066N into the container, and stirring the mixture under magnetic force in a dark place until the mixture is homogeneous and transparent, thereby obtaining a mixed coating;
[0172] (3) applying the mixed coating to a thickness of 30±1 μm on a cleaned glass slide;
[0173] (4) The coated substrate is placed under a UV-LED lamp for ultraviolet irradiation for 90 seconds to obtain a transparent coating.
[0174] The preparation process of the fluorinated polyurethane acrylate oligomer comprises the following steps:
[0175] Under the protection of N2 atmosphere, 1.0g (0.5mmol) of perfluoropolyether diol FD-164 (Mn=2000g / mol), 9g (4.5mmol) of dehydrated polycarbonate diol PH-200 (Mn=2000g / mol), and 2.24g (10mmol) of isophorone diisocyanate were added into a three-necked flask in sequence, and 0.3% of dibutyltin dilaurate was added. The mechanical stirring speed was 300rpm, and the mixture was reacted at 80°C for 3h. The NCO% was titrated to reach the theoretical value, and then 2.98g (10mmol) of the end-capping agent pentaerythritol triacrylate and 0.05% of 4-methoxyphenol were added dropwise. The mixture was reacted at 70°C for 4h. The reaction was terminated when the titration NCO% was ≤0.06%, and a fluorine-containing polyurethane acrylate oligomer was obtained.
[0176] The structural formula of the fluorourethane acrylate oligomer is the same as that of Example 2.
[0177] Comparative Example 3
[0178] (1) Clean the surface of the slide and dry it for later use;
[0179] (2) adding 1.0 g (14.86%) isobornyl acrylate and 0.5 g (7.43%) modified silica sol to 5.0 g (74.29%) fluorinated polyurethane acrylate oligomer, and letting the mixture stand in a container for 30 min, adding 0.20 g (2.97%) photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone, 0.01 g (0.15%) leveling agent BYK-3455 and 0.02 g (0.3%) defoaming agent AT-99 to the container, and stirring the mixture under magnetic force in the dark until the mixture is homogeneous and transparent to obtain a mixed coating;
[0180] (3) applying the mixed coating to a thickness of 30±1 μm on a cleaned glass slide;
[0181] (4) The coated substrate is placed under a UV-LED lamp for ultraviolet irradiation for 90 seconds to obtain a transparent coating.
[0182] The preparation process of the fluorinated polyurethane acrylate oligomer comprises the following steps:
[0183] Under the protection of N2 atmosphere, 0.65g (0.5mmol) of perfluoropolyether diol FD-163 (Mn = 1300g / mol), 9g (4.5mmol) of dehydrated polycarbonate diol BH-200 (Mn = 2000g / mol), and 2.24g (10mmol) of isophorone diisocyanate were added to a three-necked flask in sequence, and 0.3% of dibutyltin dilaurate was added. The mechanical stirring speed was 300rpm, and the reaction was carried out at 80°C for 3h. The NCO% was titrated to reach the theoretical value, and then 5.24g (10mmol) of dipentaerythritol pentaacrylate was added dropwise as a capping agent and 0.1% of 2,6-di-tert-butyl-p-methylphenol. The reaction was carried out at 70°C for 4h. The reaction was terminated when the titration NCO% was ≤0.06%, and a fluorine-containing polyurethane acrylate oligomer was obtained.
[0184] The structural formula of the fluorine-containing polyurethane acrylate oligomer is the same as that of Example 3.
[0185] Comparative Example 4
[0186] (1) Clean the surface of the slide and dry it for later use;
[0187] (2) adding 0.5 g (16.03%) of diethylene glycol diacrylate to 2.5 g (80.13%) of fluorinated polyurethane acrylate oligomer and letting the mixture stand in a container for 30 min, adding 0.1 g (3.2%) of photoinitiator 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, 0.01 g (0.32%) of leveling agent BYK333 and 0.01 g (0.32%) of defoaming agent AS-6800 to the container, and stirring the mixture in a dark place with magnetic force until the mixture is homogeneous and transparent to obtain a mixed coating;
[0188] (3) applying the mixed coating to a thickness of 30±1 μm on a cleaned glass slide;
[0189] (4) The coated substrate is placed under a UV-LED lamp for ultraviolet irradiation for 90 seconds to obtain a transparent coating.
[0190] The preparation process of the fluorinated polyurethane acrylate oligomer comprises the following steps:
[0191] Under the protection of N2 atmosphere, 0.52g (0.5mmol) perfluoropolyether diol Wuhan Lana Bai 1937 (Mn = 1040g / mol), 9g (4.5mmol) dehydrated polycarbonate diol G3452 (Mn = 2000g / mol), 2.24g (10mmol) isophorone diisocyanate were added to a three-necked flask in sequence, and 0.3% dibutyltin dilaurate was added. The mechanical stirring speed was 300rpm, and the reaction was carried out at 80 ° C for 3h, and the NCO% was titrated to reach the theoretical value, and then 0.65g (5mmol) hydroxyethyl methacrylate and 1.49g (5mmol) pentaerythritol triacrylate were added dropwise as end-capping agents and 0.05% hydroquinone, and the reaction was carried out at 70 ° C for 4h. The reaction was terminated by titration of NCO% ≤ 0.06%, and a fluorinated polyurethane acrylate oligomer was obtained.
[0192] The structural formula of the fluorine-containing polyurethane acrylate oligomer is the same as that of Example 4.
[0193] Comparative Example 5
[0194] (1) Clean the surface of the slide and dry it for later use;
[0195] (2) adding 1.0 g (16.31%) of dicyclopentenyl acrylate to 5.0 g (81.57%) of fluorinated polyurethane acrylate oligomer in a container and letting it stand for 30 min, adding 0.1 g (1.63%) of photoinitiator 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester, 0.01 g (0.16%) of leveling agent BYK-3455 and 0.02 g (0.33%) of defoaming agent AFE-1430 into the container, and stirring with magnetic force in the dark until homogeneous and transparent to obtain a mixed coating;
[0196] (3) Apply the mixed coating to a thickness of 30±1 um on a cleaned glass slide.
[0197] (4) The coated substrate is placed under a UV-LED lamp for ultraviolet irradiation for 90 seconds to obtain a transparent coating.
[0198] The preparation process of the fluorinated polyurethane acrylate oligomer comprises the following steps:
[0199] Under the protection of N2 atmosphere, 0.65g (0.5mmol) of perfluoropolyether diol FD-163 (Mn=1300g / mol), 9g (4.5mmol) of dehydrated polycarbonate diol PC06349 (Mn=2000g / mol), and 2.24g (10mmol) of isophorone diisocyanate were added into a three-necked flask in sequence, and 0.3% of dibutyltin dilaurate was added. The mechanical stirring speed was 300rpm, and the mixture was reacted at 80°C for 3h. The NCO% was titrated to reach the theoretical value, and then 0.65g (5mmol) of hydroxyethyl methacrylate and 2.62g of dipentaerythritol pentaacrylate were added dropwise as end-capping agents and 0.1% of 4-methoxyphenol. The mixture was reacted at 70°C for 4h. The reaction was terminated when the titration NCO% was ≤0.06%, and a fluorine-containing polyurethane acrylate oligomer was obtained.
[0200] The structural formula of the fluorine-containing polyurethane acrylate oligomer is the same as that of Example 5.
[0201] Comparative Example 6
[0202] (1) Clean the surface of the slide and dry it for later use;
[0203] (2) adding 0.5 g (16.03%) 1,6-hexanediol diacrylate to 2.5 g (80.13%) fluorine-containing polyurethane acrylate oligomer in a container and letting it stand for 30 min, adding 0.1 g (3.2%) photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 0.01 g (0.32%) leveling agent BYK-3550 and 0.01 g (0.32%) defoaming agent BYK-066N into the container, and stirring with a magnetic force in the dark until the mixture is homogeneous and transparent to obtain a mixed coating;
[0204] (3) Apply the mixed coating to a thickness of 30±1 um on a cleaned glass slide.
[0205] (4) The coated substrate is placed under a UV-LED lamp for ultraviolet irradiation for 90 seconds to obtain a transparent coating.
[0206] The preparation process of the fluorinated polyurethane acrylate oligomer comprises the following steps:
[0207] Under the protection of N2 atmosphere, 0.3g (0.5mmol) perfluoropolyether diol FD-162 (Mn = 600g / mol), 9g (4.5mmol) dehydrated polycarbonate diol MNF3230 (Mn = 2000g / mol), and 2.24g (10mmol) isophorone diisocyanate were added to a three-necked flask in sequence, and 0.3% dibutyltin dilaurate was added. The mechanical stirring speed was 300rpm, and the reaction was carried out at 80°C for 3h. The NCO% was titrated to reach the theoretical value, and then 2.62g (5mmol) dipentaerythritol pentaacrylate and 1.49g (5mmol) pentaerythritol triacrylate were added dropwise as end-capping agents and 0.05% 2,6-di-tert-butyl-p-methylphenol. The reaction was carried out at 70°C for 4h. The titration NCO% was ≤0.06%, and the reaction was completed to obtain a fluorinated polyurethane acrylate oligomer.
[0208] The structural formula of the fluorine-containing polyurethane acrylate oligomer is the same as that of Example 6.
[0209] The properties of different hybrid coatings obtained in the embodiments of the present invention and the comparative examples are shown in Table 1.
[0210] Table 1 Paint film performance test table of embodiments and comparative examples
[0211]
[0212]
[0213] Description: The coating hardness is tested according to the GBT 6739-2006 method, Mitsubishi pencil, load is 750g; the coating adhesion is tested according to the GB-T 9286-1998 method; the coating contact angle test is to place the coating sample on the contact angle measuring instrument (model: JC2000D2, provided by Shanghai Zhongchen Digital Technology Equipment Co., Ltd.), and let the quantitative injector drip 5μL deionized water to the sample surface at room temperature. Each group of samples is measured five times, and the average value is taken as the contact angle of the sample; severe scratches on the appearance of the paint film represent "×", slight scratches or no scratches represent "√"; water contact angle "none" means that the coating has been completely scratched.
[0214] As can be seen from Table 1, adding modified silica sol to the base resin greatly improves the hardness and wear resistance of the coating and slightly improves the hydrophobicity, but adding too much will also affect the coating performance.
[0215] Table 2 Anti-fingerprint properties of coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 6
[0216]
[0217]
[0218] After adding the modified silica sol, the coating is more compact, making fingerprints easier to wipe off, and the anti-fingerprint performance of the coating is improved. Anti-fingerprint performance test: The artificial fingerprint liquid is composed of 95% artificial sweat and 5% artificial sebum. The artificial sweat is prepared by mixing 3mL / L of lactic acid, 5mL / L of acetic acid, 10g / L of sodium chloride, 10g / L of sodium hydrogen phosphate and deionized water, and the artificial sebum is composed of oleic acid (2%), stearic acid (2%), and squalene (1%). After the artificial sweat and artificial sebum are mixed, a small amount of non-ionic surfactant (Triton X-100, added in an amount of 2μL / g of the mixture) is added to overcome the natural immiscibility between sweat and sebum. First, clean the finger with alcohol, immerse the finger in the artificial fingerprint liquid, and then touch the surface of the coating to form a fingerprint, and then wipe it with a paper towel at a speed of 3cm / s under a pressure of 500g load, and record the number of wipes that can make the fingerprint disappear. The results are shown in Table 2.
[0219] Table 3 Light transmittance of Examples 1 to 6 and Comparative Examples 1 to 6 at 550 nm
[0220]
[0221]
[0222] It can be seen from Table 3 that the addition of modified silica sol will enhance the transparency of the coating in the visible light region; the light transmittance of the coating was tested using an ultraviolet spectrophotometer, and according to GB / T 2680-1994, the transmittance of 12 groups of coating samples at 550nm was tested respectively.
[0223] It can be seen from the above embodiments that the present invention provides a UV-curable organic / inorganic hybrid low-fluorine wear-resistant anti-fingerprint coating and a preparation method thereof. The innovation of the present invention lies in the use of perfluoropolyether diol to modify polycarbonate diol to synthesize a new fluorine-containing polyurethane acrylate resin, which effectively improves the wear resistance, anti-fingerprint performance and transparency of the coating. At the same time, the sol-gel technology is used to prepare modified silica particles to match the ultraviolet light-curing resin system, thereby improving the compatibility of silica particles with the light-curing resin system; the resulting hybrid UV coating has a lower inorganic component and a lower fluorine content, showing high transparency, high hardness, high wear resistance and excellent anti-fingerprint performance. The water contact angle of the coating is greater than 110°, the transmittance is greater than 90%, and it can still maintain hydrophobicity after being rubbed with steel wool 2000 times; fingerprints can be removed by wiping with a paper towel less than once.
[0224] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A UV-curable organic / inorganic hybrid low-fluorine wear-resistant anti-fingerprint coating, characterized in that: Prepared from raw materials including the following mass percentages:
2. The UV-curable organic / inorganic hybrid low-fluorine-containing wear-resistant anti-fingerprint coating according to claim 1, characterized in that: The preparation method of the fluorine-containing polyurethane acrylate oligomer comprises the following steps: S1. In a N2 environment, a perfluoropolyether diol, a polycarbonate diol, a diisocyanate and an organic metal catalyst are mixed and reacted to obtain an NCO-terminated prepolymer; S2, adding a polymerization inhibitor and a capping agent monomer to the prepolymer to react to obtain a fluorine-containing polyurethane acrylate resin; The molar ratio of the perfluoropolyether diol to the polycarbonate diol is 1:5-10; the molar ratio of the polycarbonate diol to the diisocyanate is 1:1-2, and the amount of the organic metal catalyst is 0.1-2% of the total mass of the perfluoropolyether diol, the polycarbonate diol and the diisocyanate; The dosage of the polymerization inhibitor is 0.01-0.1% of the weight of the prepolymer, and the molar ratio of the diisocyanate to the end-capping agent monomer is 2:1-2.
3. The UV-curable organic / inorganic hybrid low-fluorine-containing wear-resistant anti-fingerprint coating according to claim 2, characterized in that: The perfluoropolyether diol comprises one or more of Italian SOLVAYFLUOROLINK D4000, domestic Yuyao Huihong FD-162, FD-163, FD-164 and domestic Wuhan Lanabai product number 1937; The polycarbonate diol comprises one or more of UH-200, PH-200 and BH-200 in the Ube PCDL series, Asahi Kasei G3452, G3450J, T4672, T4692, T4691 and T5652, Kuraray C-2050 and C-2090, and domestic Guangdong Wengjiang PC06349 and Munafei MNF3230; The diisocyanate comprises one or more of isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate and hexamethylene diisocyanate; and the organic metal catalyst comprises one or more of dibutyltin dilaurate, stannous octoate and organic bismuth.
4. The UV-curable organic / inorganic hybrid low-fluorine-containing wear-resistant anti-fingerprint coating according to claim 2 or 3, characterized in that: The polymerization inhibitor comprises one or more of 4-methoxyphenol, hydroquinone and 2,6-di-tert-butyl-p-methylphenol; the end-capping agent monomer comprises one or more of hydroxyethyl methacrylate, hydroxyethyl acrylate, 2-ethoxyethyl acrylate, 2-cyanoacrylate, β-hydroxypropyl acrylate, β-hydroxypropyl methacrylate, pentaerythritol triacrylate and dipentaerythritol pentaacrylate.
5. The UV-curable organic / inorganic hybrid low-fluorine-containing wear-resistant anti-fingerprint coating according to claim 4, characterized in that: In the step S1, the reaction temperature is 70-90° C., and the reaction time is 2-4 hours; in the step S2, the reaction temperature is 60-80° C., and the reaction time is 3-5 hours.
6. The UV-curable organic / inorganic hybrid low-fluorine-containing wear-resistant anti-fingerprint coating according to claim 1 or 5, characterized in that: The preparation method of the modified silica sol comprises the following steps: S3, tetraethyl orthosilicate and anhydrous ethanol are mixed at 20-40° C., and the temperature is raised while stirring. After reaching the reaction temperature, a hydrochloric acid solution catalyst is added dropwise to adjust the pH to 3-4. After the addition is completed, the reaction is continued for a certain period of time to obtain a hydrolysis solution; S4, adding silanes with different functional groups to the hydrolysis solution to react, and aging to obtain modified silica sol; In the step S3, the mixing time is 15 to 30 minutes, the reaction temperature is 30 to 50° C., and the reaction time is 2 to 3 hours; in the step S4, the reaction temperature is 50 to 70° C., the reaction time is 4 to 8 hours, and the aging time is 3 to 5 days.
7. The UV-curable organic / inorganic hybrid low-fluorine-containing wear-resistant anti-fingerprint coating according to claim 6, characterized in that: The molar ratio of the tetraethyl orthosilicate, silanes with different functional groups and anhydrous ethanol is 1:0.1-5:1-10; the silane comprises one or more of methyltrimethoxysilane, methyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, methacryloxypropyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, perfluorodecyltriethoxysilane, (3-mercaptopropyl)trimethoxysilane, tridecafluorooctyltrimethoxysilane, perfluoropolyethertrimethoxysilane, dodecyltrimethoxysilane and dodecyltriethoxysilane.
8. The UV-curable organic / inorganic hybrid low-fluorine-containing wear-resistant anti-fingerprint coating according to claim 1, 5 or 7, characterized in that: The reactive diluent comprises one or more of isobornyl acrylate, dicyclopentenyl acrylate, 1,6-hexanediol diacrylate, diethylene glycol diacrylate and trimethylolpropane triacrylate; The photoinitiator comprises one or more of 1-hydroxycyclohexyl phenyl ketone, benzoin diethyl ether, 2-hydroxy-2-methyl-1-phenylpropanone, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester; the leveling agent comprises one or more of German BYK-3455, BYK-3550 and BYK333; the defoamer comprises one or more of American Dow AFE-1430, German BYK-066N, domestic Datian AT-99 and German AS-6800.
9. The UV curable organic / inorganic hybrid low fluorine-containing wear-resistant The method for preparing an anti-fingerprint coating comprises the following steps: The fluorine-containing polyurethane acrylate oligomer, the reactive diluent, the modified silica sol, the photoinitiator, the leveling agent and the defoaming agent are mixed, kept still in a dark place and stirred until the mixture is homogeneous and transparent, thereby obtaining a sample; The sample is coated on the surface of a dry substrate and cured by ultraviolet light to obtain a UV-cured organic / inorganic hybrid low-fluorine-containing wear-resistant and anti-fingerprint coating.
10. The preparation method according to claim 9, characterized in that: The UV curing time is 30 to 300 seconds.
Citation Information
Patent Citations
Preparation method for antifogging thin film coating with high light transmission
CN103709927A
Ultraviolet curing coating and preparation method thereof, and super-hydrophilic transparent antifogging coating layer and preparation method thereof
CN105176371A
UV curing coating containing Y-type perfluoropolyether single-ended diol
CN112409912A
Fluorine-containing polyurethane acrylate resin and preparation method and application thereof
CN113201111A
Photocuring composition containing perfluoropolyether / alkenyl silicon resin and method for constructing waterproof antifouling coating
CN114369412A